Model of Efficiency Assessment of Regulation In The Banking Seсtor - I. V. Larionova (Vestnik MGIMO-Universiteta)
In this article, the modern system of regulation of the national banking sector is viewed, which, according to the author, needs theoretical judgment, structuring, disclosure of the maintenance of efficiency of functioning is considered. The system of regulation reveals on a system basis, it is offered to consider it as set of elements and the mechanism of their interaction which are formed taking into account target reference points of regulation. Thus it is emphasized that for regulation the contradiction is concluded: achievement of financial stability of functioning of the banking sector, as a rule, contains economic growth. The need for development of theoretical ideas of efficiency of regulation of the banking sector gains special relevance taking into account the latest events connected with revocation of licenses of commercial banks on implementation of bank activity, the high cost of credit resources for managing subjects, an insignificant contribution of the banking sector to ensuring rates of economic growth. The author offered criteria of efficiency of regulation of the banking sector to which are referred: functional, operational, social, and economic efficiency. Functional efficiency opens ability of each subsystem of regulation to carry out the functions ordered by the law. Operational efficiency describes correctness suffered by the regulator and commercial banks of the expenses connected with regulating influence. At last, social and economic efficiency is connected with degree of compliance of a field of activity of the banking sector to requirements of national economy, and responsibility of banking business before society. For each criterion of efficiency of regulation of the banking sector the set of the quantitative and quality indicators, allowing to give the corresponding assessment of the working model of crediting is offered. The aggregated expert assessment of the Russian system of regulation of the banking sector which is characterized as compensatory and satisfactory is given in article.